Mirror for humanity : a concise introduction to cultural anthropology - Kottak, Conrad Phillip (Boston : McGraw-Hill College, 2003)
Designed to provide a concise introduction to cultural anthropology. The book covers basics, while also illustrating prominent current issues, and places a strong emphasis on ethnicity and race, and gender issues
Includes bibliographical references and index.
Keywords: Ethnology